SYNTHESIS AND THERMAL PROPERTIES OF NOVEL MALEONITRILES - Erdogmus, Ali (YILDIZ TECHNICAL UNIV, 2016)
In this study, the synthesis and thermal properties of two novel maleonitriles bearing 8-membered heterocyclic derivatives is described first time. New maleonitriles, benzo-(1,2-bis-methylthio) maleonitrile and [Benzo-15-crown-5]-(4,5-bis-methylthio) maleonitrile have been prepared by the reaction of different alkyl halides such as 1,2-bis(brommethyl) benzene and 4,5-bis-(brommethyl)[benzo-15-crown-5] with dithiomaleonitrile disodium salt. Both compounds are characterized by IR, Mass, NMR spectroscopy as well as elemental analysis.
Keywords: Macrocycles; maleonitrile; crown ethers; thermal properties; SOLUBLE PORPHYRAZINE; LARIAT ETHERS; METAL-IONS; ALKALI; EXTRACTION; COMPLEXES; ELECTROCHEMISTRY; DERIVATIVES; POLYMERS; Engineering